Further insights into the latex metabolite profile of Ficus carica - Oliveira, A.P. (2011)
Latex is a sticky emulsion that exudes upon damage from specialized canals from several plants. It contains several biologically active compounds, such as phytosterols, fatty acids, and amino acids. In plants, these compounds are involved in the interaction between plants, insects, and the environment. Despite its chemical, biological, and ecological importance, Ficus carica latex is still poorly studied. To improve the knowledge on the metabolite profile of this matrix, a targeted metabolite analysis was performed in a representative sample from F. carica latex. Seven phytosterols were determined by gas chromatography-ion trap mass spectrometry (GC-ITMS) and high-performance liquid chromatography coupled to diode array detection (HPLC-DAD), with β-sitosterol and lupeol being the compounds present in higher concentrations (ca. 54 and 14%, respectively). A total of 18 fatty acids were characterized by GC-ITMS, being essentially represented by saturated fatty acids (ca. 86.4% of total fatty acids). A total of 13 free amino acids were also identified by high-performance liquid chromatography coupled to ultraviolet-visible spectroscopy (HPLC/UV-vis), and cysteine and tyrosine were the major ones (ca. 38.7 and 31.4%, respectively). In humans, phytosterols and some polyunsaturated fatty acids, such as linoleic acid, are known for their anticarcinogenic properties. With regard to amino acids, some of them, such as glycine, are neurotransmitters. Our results reveal the presence of a wide diversity of compounds, from distinct classes, in F. carica latex, possessing various potential pharmacological activities; thus, its biological potential appears to be worth further exploring.